Rural Finance Innovations : Topics and Case Studies - World Bank (Washington, DC, 2012)
Financial market liberalization, innovations in the area of risk management, and reductions in transaction and supervisory costs have had significant positive impacts on agricultural finance institutions. Building on these positive developments, this study will attempt to contribute ideas based on recent experiences with innovation from developing countries in order to spur more innovations in rural finance. This study focuses on four key areas where innovation could lead to greater access to agricultural finance: warehouse receipts and collateral securitization mechanisms; risk management products; supply chain finance; and, technology. The paper describes the issues surrounding the themes and how innovative techniques can be used to overcome traditional barriers to providing financial services to agriculture by reducing, either the risks associated with lending, the costs, or both. The diverse group of case studies and thematic discussions also underscore some key lessons regarding the role of government in its quest to lower costs and risk in the rural finance space.